MEDIA LITERACY AND FAKE NEWS VULNERABILITY: A STUDY OF BODO MEDI-UM STUDENTS OF BODOLAND, ASSAM - Goyary, Senwarn Sun; Daimari, Perosh Jimmy (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines digital media literacy and fake news vulnerability among 342 Bodo medium secondary school students drawn from five dis-tricts of the Bodoland Territorial Region (BTR) in Assam, India. A cross-sectional survey of students enrolled in Grades 9 to 12 was conducted and the data were analyzed using descriptive statistics, Pearson correlations and multiple linear and binary logistic regression. The findings indicate that smartphones (92.7 per cent) constitute the dominant means of digital ac-cess for these students with messaging application and video-sharing plat-forms accounting for the bulk of their daily engagement. Verification prac-tices, however, remain limited: only 19.3 per cent of the respondents re-ported that they always verify information before sharing and 45.3 per cent indicated a high likelihood of forwarding content without prior verification. Among the predictors examined, confidence in evaluating credibility emerged as the strongest predictor of feeling equipped to identify fake news (β = .29, p < .001), while a higher valuation of source checking was found to reduce the odds of high sharing risk (OR = 0.77 per step, p = .046). Students enrolled in Class 12 were found to be more than twice as likely to fall with-in the high-risk group (OR = 2.22, p = .047). Results support the need for culturally and linguistically contextualized media literacy instruction in Bodo medium schools that emphasizes source verification, teacher and parent scaffolding and attention-focused accuracy prompts.